THERAPY FOR HYPERTENSION WITH ACUPUNTURE AND HERBAL CUCUMBER (Cucumis sativus (L.)) - Kamaliyah, Yuninda Asyroful; Imandiri, Ario; Adianti, Myrna (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Hypertension or high blood pressure is an increase in systolic blood presure ≥140 mmHg and diastolic blood pressure â‰¥ 90 mmHg in a person's body, when two measurements are taken with an interval of five minutes so that the body is resting or quite calm. In TCM, hypertension is categorized into two, is called Xuan Yun (vertigo) and Tou Feng (headache). Cases of hypertension experienced by patients is the patient's blood pressure has increased 188/100 mmHg because stopped taking medicine for 2 years. The patient is classified as hypertensive with differentiated liver fire hyperactivity syndrome. Purpose: To determine the effect of acupuncture combination therapy at Shenmen (HT 7), Fuliu (KI 7), Taichong (LR 3), Xingjian (LR 2), and Yinlingquan (SP 9) herbal fruit and herbal cucumber (Cucumis sativus) in diseases hypertension. Method: Treatment of Hypertension with acupuncture and herbal therapy methods. Acupuncture therapy was carried out at Shenmen (HT 7), Fuliu (KI 7), Taichong (LR 3), points for tonification, the Point of Xingjian (LR 2) and Yinlingquan (SP 9) points for sedation. Result: The water content 0f 95% in cucumber which is a diuretic can reduce blood pressure in hypertension patient by giving cucumber herbs (Cucumis sativus) once a day, for 27 days with a dose of 150 grams of cucumber. And acupuncture theraphy 12 times, once every 2 days. Conclusion: Acupuncture and herbal therapy can be used to treat diseases in hypertension patients.